Crypto - Dysart, Derek (O'Reilly Online Learning., 2023)
The crypto era has arrived, and business will never be the same. Real applications of crypto technology are growing exponentially: cryptocurrency payments are moving frictionlessly across borders; NFTs are generating real value for creators and consumers alike; and new blockchain-enabled business models are being built around decentralized finance and Web3. What do you and your company need to know and do today to create new opportunities and avoid disruption? Crypto: The Insights You Need from Harvard Business Review will show you how innovative organizations of all kinds are embracing decentralized technology, reinventing themselves, and thriving in the new age of crypto. Business is changing. Will you adapt or be left behind? Get up to speed and deepen your understanding of the topics that are shaping your company's future with the Insights You Need from Harvard Business Review series. Featuring HBR's smartest thinking on fast-moving issues-blockchain, cybersecurity, AI, and more-each book provides the foundational introduction and practical case studies your organization needs to compete today and collects the best research, interviews, and analysis to get it ready for tomorrow.